Outcomes of transcatheter closure of ductus arteriosus in infants less than 6 months of age: a single-center experience - Gwang-Jun Choi; Jinyoung Song; Yi-Seul Kim; Heirim Lee; June Huh; I-Seok Kang (Korean Pediatric Society, 2018)
Purpose Transcatheter device closure of patent ductus arteriosus (PDA) is challenging in early infancy. We evaluated PDA closure in infants less than 6 months old. Methods We performed a retrospective review of infants less than 6 months of age who underwent attempted transcatheter device closure in our institution since 2004. To compare clinical outcomes between age groups, infants aged 6-12 months in the same study period were reviewed. Results A total of 22 patients underwent transcatheter PDA closure during the study period. Patient mean age was 3.3±1.5 months, and weight was 5.7±1.3 kg. The duct diameter at the narrowest point was 3.0±0.8 mm as measured by angiography. The most common duct type was C in the Krichenko classification. Procedural success was achieved in 19 patients (86.3%). Major complications occurred in 5 patients (22.7%), including device embolization (n=1), acquired aortic coarctation (n=2), access-related vascular injury requiring surgery (n=1), and acute deterioration requiring intubation during the procedure (n=1). Two patients had minor complications (9.1%). Twenty-four infants aged 6-12 months received transcatheter device closure. The procedural success rate was 100%, and there were no major complications. The major complication rate was significantly higher in the group less than 6 months of age (P=0.045). There was a trend toward increased major complication and procedural failure rates in the younger age group (P<0.01). Conclusion A relatively higher incidence of major complications was observed in infants less than 6 months of age. The decision regarding treatment modality should be individualized.